Validity and invariance of measurement of the satisfaction with love life scale in older adults - Caycho-Rodríguez, Tomás (2020)
In recent years, interest in satisfaction with love life (SWLL) has increased. Empirical evidence demonstrated that SWLL favors subjective well-being, physical and mental health, marital quality and stability. In this regard, the study aimed to examine evidence based on the internal structure validity, reliability, and measurement invariance of the Peruvian version of the Satisfaction with Love Life Scale (SWLLS). The participants were 323 older adults recruited from the region of San Martin (Peru) with an average age of 68.73 years (SD = 7.17). The sample comprised of 49.5% women and 50.5% men. The results supported the one-dimensional model and adequate reliability of the SWLLS. A multi-group analysis provided evidence of configural, metric, and scale invariance across genders. The findings verified the validity and reliability of the Peruvian version of the SWLLS, which can be used to measure SWLL.